KEUTAMAAN WORLD TRADE ORGANIZATION ATAS REGIONAL TRADE AGREEMENTS DALAM PERDAGANGAN INTERNASIONAL - A.D. Agung Sulistyo (Justitia et Pax, 2021)
The economic and political needs of countries in the world have provided a strong basis for the birth of the World Trade Organization (WTO). This need has also prompted many countries to form preferential agreements such as the Regional Trade Agreement (RTA). A clash between the two international trading systems is inevitable, there is the ambiguity of the relationship and inconsistency of views held, such as in discriminatory and non-discriminatory approaches. Doctrinal research was conducted to find out which agreement should take precedence over the two legal regimes. This paper concludes that international legal provisions favor the WTO Agreement over preferential agreements such as the RTA. Thus, an RTA that does not conform to the WTO legal regime should be considered contradictory.